(untitled) (Revista Contexto & Educação, 2026)
Introduction: Heart disease directly influences individuals’ quality of life. In this context, physiotherapy rehabilitation has a positive impact on health status and, based on prior knowledge, health education strategies directed at these patients may represent a key component of therapy. Objective: To analyze a group educational activity for cardiac patients undergoing physiotherapy in a cardiac rehabilitation program, evaluating its impact on knowledge and quality of life. Methods: This is a before-and-after intervention study involving eleven patients. The group received cardiorespiratory physiotherapy twice a week for five weeks and participated in a health education program with guidance related to lifestyle and health conditions, conducted once a week over the same period. Results: Eleven individuals completed the study. After the intervention, an improvement was observed in health knowledge related to their cardiovascular system pathology. In the pre-intervention period, most participants reported knowledge between fair and good, while in the post-intervention period, the classification changed to good and excellent in 72.7% of individuals. There was also an improvement in lifestyle habits, with 45.5% responding that they were excellent. No statistically significant differences were observed between the pre- and post-intervention periods in any of the domains analyzed, although an increase in the mean scores in all domains was identified after the intervention. Conclusion: The educational practice associated with a cardiovascular rehabilitation program proved effective in improving patients’ knowledge about the disease and self-care.